2022
DOI: 10.1038/s42003-022-03263-6
|View full text |Cite
|
Sign up to set email alerts
|

A functional SNP rs895819 on pre-miR-27a is associated with bipolar disorder by targeting NCAM1

Abstract: The aberrant expression or genomic mutations of microRNA are associated with several human diseases. This study analyzes the relationship between genetic variations of miRNA and schizophrenia or bipolar disorder. We performed case-control studies for ten SNPs in a total sample of 1584 subjects. All these ten SNPs were on or near mature microRNAs. We identified the association between bipolar disorder and the T/C polymorphism at rs895819. To illustrate the function of miR-27a, we constructed several miR-27a kno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…For example, the rs1321204 site on the serotonin receptor 1B (HTR1B) gene regulates the expression of HTR1B by affecting the binding of miR-96 to HTR1B, thus affecting the aggressive behavior of mice [ 28 ]. SNP rs895819, located on pre-miR-27a, is involved in the regulation of bipolar disorder by targeting neural cell adhesion molecule 1 (NCAM1) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the rs1321204 site on the serotonin receptor 1B (HTR1B) gene regulates the expression of HTR1B by affecting the binding of miR-96 to HTR1B, thus affecting the aggressive behavior of mice [ 28 ]. SNP rs895819, located on pre-miR-27a, is involved in the regulation of bipolar disorder by targeting neural cell adhesion molecule 1 (NCAM1) [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of the rs895819 SNV and its effect on its expression is unknown. Previous studies suggested that the rs895819 SNV alters the stability and/or processing of miR-27a; however, these results are conflicting, with some studies showing increased miR-27a expression [13,34], others showing decreased miR-27a expression [27,35,36], and one showing no effect of the rs895819 SNV on miR-27a expression [37]. Similarly, conflicting studies have shown a decrease, an increase, and no association between carriers of the rs895819 SNV and the risk of various cancers [16][17][18]25,38].…”
Section: Discussionmentioning
confidence: 99%